SIKAP MASYARAKAT SEKITAR MASJID TERHADAP KREASI BACKYARD FARMING BERUPA HIDROPONIK TANAMAN SAYURAN - Abiyuna, Thaufan; Supratman, Supratman; Sumarsih, Enok; Bunda, Cici Aulia Permata; Faqihuddin, Faqihuddin (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Farming activities that require love of the environment, tenacity, creativity and responsibility are expected to be able to improve the productive and independent character of program participants. The target participants for this program are teenagers who take part in the taklim assembly. Implementation methods include surveys, outreach, training, mentoring, evaluation and reporting. The survey was carried out by visiting potential partners, requesting their willingness to partner in carrying out activities and determining the time and place for socialization and training activities on hydropnic farming as a form of backyard farming. Socialization and training were carried out by inviting mosque teenagers and parents of Islamic study students who were motivated to take part in the activities. Furthermore, mentoring activities are carried out periodically until the plants are ready to be harvested. After the first harvest, several partner members were interested in continuing backyard farming activities using a hydroponic system and growing plants in pots/polybags. The results of monitoring before reporting the progress of this activity show that it is ready to harvest for the second period and the hybrid red chili plants planted in polybags have started to bear fruit. This condition indicates that the participants' motivation to carry out production activities, one of which is backyard farming, is starting to grow. It is hoped that program participants will be skilled in carrying out backyard farming and be able to develop it into an additional source of family income, so that apart from being beneficial for a greener environment, it also provides economic benefits. In order to measure the success of the program, the implementers conducted a survey via questionnaire to participants regarding the participants' attitudes towards socialization and training activities as well as towards hydroponic cultivation as a form of backyard farming practice. The results of filling out the questionnaire have been tabulated and analyzed at the next stage